(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article provides a detailed overview of the TIMSS (Trends in International Mathematics and Science Study) international assessment, including its objectives, tasks, framework, classification, and influencing factors. It highlights the types of tasks corresponding to TIMSS, the importance of this study in enhancing the effectiveness of mathematics and science education, and its role in identifying students’ knowledge, skills, and problem-solving abilities.